The link between atrial fibrillation and hereditary channelopathies - El-Battrawy, Ibrahim; Lang, Siegfried; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Europace, 2018)
The article by De With et al.1 published in Europace describing the clinical profile, atrial fibrillation (AF) progression, and outcome of patients with young-o
Gesehen am 02.10.2019